Used of RASCH Model for Analysis of Students' Critical Thinking Skills Test Instruments on Thermochemical Topics - Rizka Fahreza; Sandy Yudha; Rudi Purwanto; Retno Dwi Suyanti; Ayi Darmana (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: This study is descriptive study with quantitative approach. Sample determination by proportional sampling. The investigated variables are student abilities, which are reflected in end-of-semester exam results in chemistry courses. In this study, experimental method was used as a means of data collection. The test instrument uses a two-part multiple-choice model with a total of 30 items and five answer options. Using RASCH to evaluate models for testing students' critical thermal materials. This study was conducted to evaluate an experimental instrument on the critical thinking skills of SMA Negeri 1 Binjai Chemistry students. 25 students will participate in the workshop. The questions will be presented in multiple choice format, with a total of 30 questions on Thermochemistry. Rasch model is used to get the appropriate items. Analysis was performed using WinSteps software. The output of the Winsteps version 4.3.2 software found 12 incorrect items and 13 correct items, resulting in a final score of 13. Based on the analysis of write maps, students with 14 codes were known to have greater abilities or talents. 02, 04 and 18 have the lowest probability. Keywords: fit, rasch model, winsteps, reliability, Critical Thinking Skills Albstralk: Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Penentuan sampel secara proporsional sampling. Variabel yang diteliti adalah kemampuan mahasiswa yang tercermin dari hasil ujian akhir semester pada mata kuliah kimia. Dalam penelitian ini, metode eksperimen digunakan sebagai alat pengumpulan data. Instrumen tes menggunakan model pilihan ganda dua bagian dengan jumlah 30 item dan lima pilihan jawaban. Menggunakan RASCH untuk mengevaluasi model untuk menguji bahan termal kritis siswa. Penelitian ini dilakukan untuk mengevaluasi instrumen eksperimen terhadap kemampuan berpikir kritis siswa Kimia SMA Negeri 1 Binjai. Sebanyak 25 siswa akan mengikuti workshop tersebut. Soal akan disajikan dalam format pilihan ganda, dengan total 30 soal tentang Termokimia. Model rasch digunakan untuk mendapatkan item yang sesuai. Analisis dilakukan dengan menggunakan software WinSteps. Output dari software Winsteps versi 4.3.2 ditemukan 12 item salah dan 13 item benar, sehingga menghasilkan skor akhir 13. Berdasarkan analisis menulis peta, siswa dengan 14 kode diketahui memiliki kemampuan atau bakat yang lebih besar. 02, 04 dan 18 memiliki probabilitas terendah. Kaltal Kunci: fit, model rasch, winsteps, reliabilitas, Kerampilan Berfikir Kritis